Assistance Of Pregnant Mothers In Preparation For Labor - Khanifah, Milatun (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Indonesia is ranked first with the highest maternal mortality rate (AKI) of 181 countries. The main causes of maternal death in Indonesia are bleeding (28%), eclampsia (13%), and complications of abortion (11%), sepsis (10%) and prolonged labor (9%). The cause can actually be prevented by adequate pregnancy checks. One effort that encourages behavior change and provides pregnant women with the knowledge and provision of physical training to prepare for labor during Trimester III. The methods used in community service are lectures, question and answer discussions, examination of pregnant women, demonstrations of pregnancy exercises, especially pelvic rocking movements. The six-month activity is carried out in the laboratories of the UMPP DIII Midwifery Study Program and Puskesmas Hall Kedungwuni II, Pekalongan Regency. The results of activities went smoothly including antenatal care examinations, trimester III pregnancy discomfort counseling, pregnancy danger signs, childbirth preparation, physical exercises including pelvic rooking, breathing exercises and trimester III pregnancy exercises. Participants showed high enthusiasm in asking and following physical exercise movements in pregnancy.